Etude de la mortalite des ovins dans les hauts plateaux ethiopiens de 1982 a 1986 - Njau, B.C.; Kasali, O.B.; Scholtens, R.G.; Degefa, M. (1988)
Analyses the frequency and causes of deaths observed during 1982-86 in sheep flocks around Debre Berhan, Ethiopia. Includes data on annual crude death rates, causes of mortality, frequency, age at death, and seasonal crude death rates.